KEKERASAN DALAM KITAB SUCI Dikehendaki dan Di-amin-i Allah? - Tantiono, Paulus T. (Universitas Katolik Santo Thomas Sumatera Utara, 2002)
It is understandable, that many religious people are so offended by the violence of God as expressed, for example, in the notion of God warrior of war, of God as angry, the notion of hell; that they are troubled in reading or praying the psalms, or the Bible. These notions are quite contrary to the idea of God in the New Testament as the Compassionate God, the Loving One, the Ever Forgiving God, The God-Father who always wait for His lost-children to return home, etc. How one could perceive violence throughout the Bible related to God? Does God have two-fold faces ? The Good One and the Violent One ?